Swimming pool attendance and respiratory symptoms and allergies among Dutch children. Issue 11 (4th August 2012) - Jacobs, José H; Fuertes, Elaine; Krop, Esmeralda J M; Spithoven, Jack; Tromp, Peter; Heederik, Dick J J
Abstract : Objectives: To describe associations among swimming, respiratory health, allergen sensitisation and Clara cell protein 16 (CC16) levels in Dutch schoolchildren. Trichloramine levels in swimming pool air were determined to assess potential exposure levels. Methods: Respiratory health and pool attendance information was collected from 2359 children, aged 6–13 years. Serum from 419 children was tested for allergen sensitisation and CC16 levels. Trichloramine levels were assessed in nine swimming facilities. Results: Trichloramine levels ranged from 0.03 to 0.78 mg/m 3 (average 0.21 mg/m 3 ). Reported swimming pool attendance and trichloramine exposure were both not associated with asthma, wheezing, rhinitis or CC16 levels. Birch and house dust mite sensitisation were associated with recent indoor swimming (OR>1.86), but not after considering recent swimming frequency multiplied by trichloramine levels. Sensitisation to house dust mites was associated with frequent baby swimming (ORs=1.75; 95% CI 1.09 to 2.79). Furthermore, sensitisation was associated with lower serum CC16 levels. CC16 levels were associated with average trichloramine concentrations in pools; however, not after considering swimming frequency multiplied by trichloramine levels. Conclusions: Measured trichloramine levels were comparable with other studies but lower than in an earlier Dutch study. Swimming pool attendance was not associated with respiratory symptoms. The association between sensitisation and swimming during the first 2 years of life suggests that early-life exposures might be important, although this needs further study. The interpretation of transient and chronic changes of CC16 and other inflammatory markers in relation to the pool environment and health impacts warrants further investigation. Detailed comparisons with other studies are limited as few studies have measured trichloramine levels.